Investment accounts among conventional banking accounts: simulation or innovation - Sadique, Muhammad Abdurrahman (WorldConferences.net, 2017)
Initiation of joint investment accounts operating on a profit and loss sharing basis could be regarded as a major innovation by Islamic banks in the practice of Islamic finance. Provided as an alternative to conventional interest based accounts such as fixed deposit accounts and saving accounts, these facilitate clients to invest their surplus resources through the mediation of the bank for realising profits. Operation of equity accounts where investment is done by the public at varying points of time for jointly sharing in profit and loss periodically involves several aspects ofIslamic legal importance concerning joint investment. While the modus operandi of investment accounts appear to have gained market acceptance, theoretical and Shari‘ah aspects continue to demand the interest of academics. Whether these accounts differ from conventional bank accounts in substance and outcome as well as Shari‘ah validity may vary depending on diverse factors, and requires careful individual scrutiny.